Cooperative employment cycles in Spain. Does regional localization matter? - Sala-Ríos, Mercè; Farré-Perdiguer, Mariona; Torres-Solé, Teresa (REVESCO. Revista de Estudios Cooperativos, 2020)
This paper presents a territorial analysis of the cooperatives within various Spanish regions. The purpose is threefold. The first objective is to investigate whether the cooperatives’ employment cycle shows a different relationship regarding the business cycle and whether this depends on the regional localization of the cooperatives. The second is to evaluate whether the greater the cooperative tradition, the greater the decoupling between business cycle and cooperatives’ cyclical phases. The third objective is to find out if, within the different Spanish regions, those cooperatives that survived the 2008 crisis share some common patterns. Our results show that (1) more than 50% of the regions achieve a medium degree of a pro-cyclical relationship and that only a small group of regions presents a counter-cyclical relationship; (2) the cooperatives’ employment exhibits a certain degree of resilience; and (3) the cooperatives that survived the crisis were mature, small-sized firms with adequate financial ratios but with a negative profit margin.